Penerapan Akuntansi dalam Rumah Tangga : Studi Fenomenologi pada Ibu-ibu Rumah Tangga di Desa Maulo’o Kecamatan Paga Kabupaten Sikka - Maria Adinda Nona Febi; Wilhelmina Mitan; Fransiscus De Romario (Journal Of Business, Finance, and Economics (JBFE), 2024)
This study aims to examine the role of accounting in the Maulo'o Village community and how accounting is applied in households regarding four important things, namely budgeting, recording, decision making and long-term planning. This study uses a qualitative method with a phenomenological study approach. The results of the study indicate that the application of accounting in households plays a very important role in people's lives. The important role of accounting and the benefits of accounting in household life are useful for stabilizing household finances, controlling expenses and prioritizing primary needs and preventing families from debt activities. The application of accounting in the decision-making practices of eight housewife informants in Maulo'o Village always discusses with her husband in making decisions and also prioritizes primary needs such as children's education costs and does not forget to always save for future needs.